2008
DOI: 10.1111/j.1439-0329.2007.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Pityogenes bidentatus and fungi in young managed Scots pine stands in Poland

Abstract: The association between Pityogenes bidentatus and fungi was studied in young, managed Pinus sylvestris stands in Poland. Fungi were isolated from emerged adults and their galleries collected from four populations. In total, 2089 fungal isolates including 42 species, were obtained. Penicillium sp. 1 and Geosmithia sp. 1 were the most commonly isolated fungi from beetles (49% and 41% of beetles respectively). Geosmithia sp. 1 species was the dominant species in P. bidentatus galleries with a frequency of occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…Also, other ophiostomatoid fungi were isolated at very low frequencies. Relatively weak relationships with blue-stain fungi were similar to those recorded for Pityogenes bidentatus (Herbst, 1784) (Jankowiak & Rossa 2008) and P. quadridens (Hartig, 1834) (Mahiesen-Käärik 1953) on Pinus sylvestris L. In Polish studies (Jankowiak & Rossa 2008), P. bidentatus carried ophiostomatoid species very rarely and this bark beetle was frequently associated with fungi of the genus Geosmithia. In our study we also relatively often isolated these fungi from P. pityographus beetles and galleries.…”
Section: Discussionmentioning
confidence: 53%
“…Also, other ophiostomatoid fungi were isolated at very low frequencies. Relatively weak relationships with blue-stain fungi were similar to those recorded for Pityogenes bidentatus (Herbst, 1784) (Jankowiak & Rossa 2008) and P. quadridens (Hartig, 1834) (Mahiesen-Käärik 1953) on Pinus sylvestris L. In Polish studies (Jankowiak & Rossa 2008), P. bidentatus carried ophiostomatoid species very rarely and this bark beetle was frequently associated with fungi of the genus Geosmithia. In our study we also relatively often isolated these fungi from P. pityographus beetles and galleries.…”
Section: Discussionmentioning
confidence: 53%
“…We tried to induce production of perithecia by adding sterilized pine twigs in 2% water agar and 1.5% oatmeal agar (Zhou, De Beer, & Wingfield, ), without success. Although H. dematioides has been reported as fungus associated with bark beetles (Jankowiak & Bilański, ; Jankowiak & Rossa, ; Lieutier et al., ; Masuya et al., ; Solheim & Långström, ), it lacks authentic specimen as well as the sequences of ex‐type strain (Thambugala et al., ); therefore, the 14 strains are determined here as S. polyspora according to the one‐fungus one‐name rule.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that H. dematioides could be introduced into host trees by Tomicus species such as T. piniperda and T. minor , as well as other bark beetle species, such as Ips cembrae (Heer), Pityogenes bidentatus (Herbst) and Crypbalus piceae (Ratz.) (Jankowiak & Kolařík, ; Jankowiak & Rossa, ; Jankowiak, Rossa, & Mista, ). In this study, S. polyspora has been isolated from the bark beetles and galleries of T. yunnanensis , which showed that S. polyspora could associate to T. yunnanensis in its lifecycle stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillium spp. have been frequently isolated from several species of bark beetles [53,61,82]. Anemochory is considered the main dispersion method for this genus, being the association between Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%